Currículo de pedagogia : discursos e implicações na formação de professores para a diversidade cultural - Souza, Alessandra Genro de (2011)
Issues related to cultural diversity and multiculturalism have grown considerably in recent years in our country, especially after the promulgation of the Constitution of 1988, which marks a significant advance in the recognition of cultural plurality existing in the formation of the Brazilian people. This involves placing the culture on which rests the formation of our people, including in the educational field, particularly through the analysis of the curriculum. Rethinking education and by extension the curriculum, demand a new analysis regarding the place of cultural diversity in the path of students, from kindergarten through higher education. This study aims to analyze the discourses on teacher training for the cultural diversity that is stamped in the daily teaching and make educational policy. To that end, contextualized ways to predict, design and realize the curriculum, in their different nuances, with emphasis on thinking curriculum and diversity as understood in educational policies. For the realization of the study, we adopted the literature in their input document, so were the focus of research and analysis of the National Curriculum Guidelines (DCN) for the School of Education and the opinions of the National Council of Education, and implemented curricular courses in pedagogy in Brazil. Studies have shown that the DCN showed a general speech about stamp of cultural diversity which is expressed in the texts of the curriculum policy, since such texts are off to a precise definition of the issue and thus leave vague the idea reflective teacher education in relation to multicultural issues that are established in the process of learning and the trajectory of the professor who is in constant training. Thus, the generalist discourse fades away, without a specific focus for solid teacher training and, consequently, for her performance in the classroom. Ponder is finally possible implications in teacher education, based on different conceptions of hegemonic conceptions of society, culture and curriculum, and how these ideas came the process of teaching and learning that goes from higher education for initial year in which the teacher will act